Hubungan antara Pemberian Kompensasi dengan Disiplin Kerja pada Guru Pegawai Negeri Sipil (PNS) Rayon III di Kecamatan Muara Sugihan Kabupaten Banyuasin - Rosyidah, Ulfa; Budiman, Budiman; Setiawan, Kiki Cahaya (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, Sumatra Selatan, 2021)
This study aims to determine the relationship between compensation and work discipline for Civil Servant Teachers (PNS) in District III of Muara Sugihan District, Banyuasin Regency by using a correlational quantitative research approach. The hypothesis proposed in this study is that there is a relationship between compensation and work discipline for Civil Servant Teachers (PNS) in District III of Muara Sugihan District, Banyuasin Regency. The research sample was 33 respondents. The data analysis method used is a simple regression analysis technique and uses the SPSS Version 22 for windows program. The results of the study state that there is a significant relationship between compensation and work discipline as indicated by the correlation coefficient value of 0.024 with a significant value of 0, 000 where p <0.05, this result shows that compensation for civil servant teachers has a relationship with work discipline in teachers Civil servants in District III of Muara SugihanDistrict, Banyuasin Regency.